2011
DOI: 10.1124/dmd.111.042911
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hepatic Glutathione Transferase Mu 1 and Theta 1 Activities in Humans and Mice Using Genotype Information

Abstract: ABSTRACT:We investigated the impact of glutathione transferases Mu 1 (GSTM1)-and glutathione transferase Theta 1 (GSTT1)-null genotypes on hepatic GST activities in humans and compared the results with those of Gstm1-and Gstt1-null mice. In liver with GSTM1/Gstm1-null genotype, GST activity toward p-nitrobenzyl chloride (NBC) was significantly decreased in both humans and mice. In addition, in liver with GSTT1/Gstt1-null genotype, GST activity toward dichloromethane (DCM) was significantly decreased in both hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…For example, comparison of the activity of extracts from GstmD/D mice and Gstm12/2 mice indicates that Gstm2 through Gstm7 do not contribute significantly to the metabolism of DCNB, even though the expression of Gstm2, Gstm3, Gstm6, and Gstm4 in the liver has been reported (Knight et al, 2007). Interestingly, metabolism of DCNB by human GSTM1 has not been supported in comparative studies using extracts from individuals carrying the null GSTM1 allele (Arakawa et al, 2012). Therefore, this substrate may be highly specific for a single murine Gstm1 gene, calling into question the evolutionary and functional relationship between the mouse and human Gstm isoforms (Board, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, comparison of the activity of extracts from GstmD/D mice and Gstm12/2 mice indicates that Gstm2 through Gstm7 do not contribute significantly to the metabolism of DCNB, even though the expression of Gstm2, Gstm3, Gstm6, and Gstm4 in the liver has been reported (Knight et al, 2007). Interestingly, metabolism of DCNB by human GSTM1 has not been supported in comparative studies using extracts from individuals carrying the null GSTM1 allele (Arakawa et al, 2012). Therefore, this substrate may be highly specific for a single murine Gstm1 gene, calling into question the evolutionary and functional relationship between the mouse and human Gstm isoforms (Board, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Gstm1-and Gstt1-null mice have been developed by our group (Fujimoto et al, 2006(Fujimoto et al, , 2007, since null genotypes of human GSTs have been reported to occur exclusively in GSTM1 and GSTT1 (Hayes et al, 2005). Gstm1-and Gstt1-null mice have the potential to be relevant models of humans with GSTM1-and GSTT1-null genotypes, since we showed the functional similarity between humans and mice for GSTM1 and GSTT1 toward some substrates (Arakawa et al, 2012). In addition, the resistance to APAP-induced hepatotoxicity in Gstp1/p2-null mice, which was described previously, prompted us to perform a study of APAP using Gst-null mice.…”
mentioning
confidence: 64%
“…Some individuals characterized, for example, by double null M1 and T1 mutation, endowed with a decreased level of GST activity, may experience a lower formation of conjugates and a longer half-life of the parent compound, resulting in a higher risk of MC-induced toxic effects, especially when combined to GSH depletion. The use of knockout mouse strains may potentially help in understanding the relevance of human null phenotype and its covering by the inter-individual variability default factor of 10, but it is known that, depending on the used substrate, the impact of GST-null genotypes in human and mice is not always the same (Arakawa et al, 2012). Therefore the use of phenotyped human cytosol samples could be useful.…”
Section: Discussionmentioning
confidence: 99%